The issue of motivation for foreign languages learning in international research works: Scoping review - I. K. Tsalikova; S. V. Pakhotina (Russian State Vocational Pedagogical University, 2021)
Introduction. Today, foreign language competence of a person is a necessary means of active social and professional life. Despite this, quite a lot of young people do not always have the desire to learn foreign languages. This paradox made the motivation to learn foreign languages a popular issue to research worldwide. The article presents the scoping review of international studies devoted to the issue of motivation to learn foreign languages. First of all, it is necessary to understand the research trends in the study of this issue in general, and to determine factors, which influence the lack of students' interest to learn foreign languages in particular.The aim of the present research is to outline the current focus trends and to define the gaps in international research papers aimed at investigating the issue of motivation for foreign languages learning.Methodology and research methods. The methodological framework of the current research is based on the qualitative content analysis of relevant empirical research on this issue from the periodicals indexed by the international databases Scopus and Web of Science over the last 15 years. This review will provide an understanding of the degree of knowledge of the analysed issues at the international level.Results. The research works on the issues of motivation for foreign languages learning were divided into two main categories: the research works concentrated on inner - academic and professional factors, and the works which deal with the outer - social factors of influence. Within these groups, the existing research trends and the most promising research areas were identified (for instance, the influence of peers on the motivational sphere of students). Amongst the numerous works investigating external (socio-economic) factors of influence, there is insufficient research on the influence of macro-political and macro-economic factors on the motivation for learning languages (for instance, foreign languages learning preferences). The research outcomes will contribute to understanding the factors, which influence the students' lack of interest in learning foreign languages.The scientific novelty is in the originality of the demonstrated review, which includes many scientific papers performed by scientists from all over the world and based on various research procedures. In the review, the geographical principle of data selection was not used and the publication date was not taken into account. The main selection criterion was a research paper to be published in a journal peer-reviewed by international databases over the last 15 years.Such a principle was necessary to understand research trends in the issue of motivation for mastering a foreign language competence and to determine similar (or specific) factors for different countries, which cause students' lack of interest in learning foreign languages.Practical significance. The results of the obtained analysis will give understanding of the reasons for the lack of students' motivation to study foreign languages. Moreover, it will help to find a solution to this international challenge.